Antiaging Mechanism of Natural Compounds: Effects on Autophagy and Oxidative Stress - Elizabeth Taylor; Yujin Kim; Kaleb Zhang; Lenne Chau; Bao Chieu Nguyen; Srujana Rayalam; Xinyu Wang (Molecules, 2022)
Aging is a natural biological process that manifests as the progressive loss of function in cells, tissues, and organs. Because mechanisms that are meant to promote cellular longevity tend to decrease in effectiveness with age, it is no surprise that aging presents as a major risk factor for many diseases such as cardiovascular disease, neurodegenerative disorders, cancer, and diabetes. Oxidative stress, an imbalance between the intracellular antioxidant and overproduction of reactive oxygen species, is known to promote the aging process. Autophagy, a major pathway for protein turnover, is considered as one of the hallmarks of aging. Given the progressive physiologic degeneration and increased risk for disease that accompanies aging, many studies have attempted to discover new compounds that may aid in the reversal of the aging process. Here, we summarize the antiaging mechanism of natural or naturally derived synthetic compounds involving oxidative stress and autophagy. These compounds include: 2-cyano-3,12-dioxoolean-1,9-dien-28-oic acid (CDDO) derivatives (synthetic triterpenoids derived from naturally occurring oleanolic acid), caffeic acid phenethyl ester (CAPE, the active ingredient in honey bee propolis), xanthohumol (a prenylated flavonoid identified in the hops plant), guggulsterone (a plant steroid found in the resin of the guggul plant), resveratrol (a natural phenol abundantly found in grape), and sulforaphane (a sulfur-containing compound found in cruciferous vegetables).